GAMIFICATION VOCABULARY LEARNING: THE USE OF WORDWALL.NET IN JUNIOR HIGH SCHOOL - Mutmainnah Hayati; Mochtar Marhum; Hastini Hastini; Jamiluddin (Universitas Muhammadiyah Makassar, 2025)
Many approaches can be employed in vocabulary teaching and learning. One of these approaches is gamification. The goals of the study are to see if gamification approach through wordwall.nets’ utilization can increase students' vocabulary mastery and to pinpoint the word category that demonstrates the most progress. Using a pre-experimental design with a one-group pre-test and post-test model, this study assesses if word wall media can deepen students' vocabulary proficiency, and also investigates which category of content words exhibits the most gains after the platform is implemented. The population in this study are eighth-grade students from MTs Negeri 2 Palu, sampled VIII D class, and the sample was chosen using purposive sampling technique. The data was analyzed using the paired sample t-test. Data analysis reveals a clear distinction between the students' pre-test and post-test outcomes. The average of students’ results on the pre-test rises from 36.04 to 52.2 on the post test. The paired sample t-test demonstrates a statistically significant increase in the pre-test and post-test scores (Sig (2-tailed) = 0.000). This supports the alternative research hypothesis (Ha). Indicating wordwall.net is a useful tool for enhancing the vocabulary skills of eighth-grade students at MTs Negeri 2 Palu. The findings also confirms adjective as the content word that has impressive progress after the platforms’ application.